Territorial practices of urban middle class: Jardim Icarai (Icaraí Garden) in Niterói/RJ - Nunes, Brasilmar Ferreira (2013)
In this paper we discuss, from the thought of Georg Simmel’s , some assumptions about the meaning of the residential space in the contemporary modern metropolis for its occupants, particularly as a mechanism of social classification. Favoring authors of social science, we have tried to articulate different approaches that, in our interpretation, are self-complementary and that would help us to understand urban social logic. In order to illustrate our reflections we took as a reference a middle class area in Niteroi, RJ whose characteristics provided us with the necessary background to elaborate some considerations.